Transition control by micron-sized roughness elements: stability analyses and wind tunnel experiments. (1st January 2013) - Vermeersch, Olivier; Arnal, Daniel; El Din, Itham Salah
This paper presents an experimental study of cross-flow transition control on a swept wing by micron-sized roughness elements. The process consists in using an array of micron-sized roughness elements placed close to the leading edge to damp the amplitude of cross-flow instabilities and thus delay the laminar to turbulent transition. This phenomenon is studied on the pressure side of the DTP-B model placed in the Onera Fauga-Mauzac F2 wind tunnel. The sweep angle was fixed at ϕ = 40° for different angles of attack AoA = 5, 6, 7° and a velocity range varying between 60 and 90 (m/s). The influence of several geometrical parameters, such as the spacing and height of control devices, on transition delay has been investigated. Total pressure probing has been used in order to characterise the wavelength of natural (without control) cross-flow instabilities but also the one of disturbances generated by roughness elements. Both naphthalene visualisations and infra-red imaging have been used to locate the transition.